Use of multinodal explants for micropropagation of Leucadendron ‘Safari Sunset’ - Suárez, E.; Pérez-Francés, J. F.; Rodríguez-Pérez, J. A. (Spanish Journal of Agricultural Research, 2010)
Leucadendron 'Safari Sunset' is one of the most valuable Proteaceae cultivar, due to its economic importance as cutflower. In vitro tissue culture of this cultivar and others may offer a massive cloned plant production that permit to satisfy the market demand. Multinodal explants of Leucadendron 'Safari Sunset' were established in vitro on a half strength Murashige and Skoog medium supplemented with 2.2 µM benzylaminopurine (BAP). Various antioxidant treatments were used to reduce the presence of phenolic compounds in culture. No important differences in growth and multiplication between these treatments were detected during in vitro establishment and multiplication, but explants cultured on a medium with 1 g L–1 of polyvinylpyrrolidone (PVP) developed a higher number of buds in the establishment phase. Proliferation of axillary shoots was achieved with 0.88 µM BAP, being slightly higher on a medium with 2.2 µM BAP although the buds were deformed, showing abnormal leaves. The use of phytagel in this phase increased proliferation rate and shoot growth. Low percentages rooting were obtained when microcuttings were cultured on the same basal medium supplemented with several indole-3-butyric acid (IBA) concentrations. The best rooting percentage (37.5%) was obtained with 44.1 µM IBA. This work shows that micropropagation of L. 'Safari Sunset' is possible with multinodal explants, although is necessary to optimize the protocol for commercial applications.